Bidirectional Ventricular Tachycardia Due to Digitalis Intoxication - Scarduelli Luciano, Karila; Souza Bogo, Victoria; Schulze, Milena Luisa; de March Ronsoni, Rafael (JOURNAL OF CARDIAC ARRHYTHMIAS, 2021)
Bidirectional ventricular tachycardia (BDVT) is defined by beat-to-beat alternation of the QRS axis on the electrocardiogram. Its diagnosis is uncommon, and the most characteristic etiology is digitalis intoxication (DI). We report the case of a patient with heart failure of valve origin admitted for sepsis that progressed to BDVT and death, associated with DI.